2017
DOI: 10.3389/fpls.2017.01164
|View full text |Cite
|
Sign up to set email alerts
|

PLC-Mediated Signaling Pathway in Pollen Tubes Regulates the Gametophytic Self-incompatibility of Pyrus Species

Abstract: Among the Rosaceae species, the gametophytic self-incompatibility (GSI) is controlled by a single multi-allelic S locus, which is composed of the pistil-S and pollen-S genes. The pistil-S gene encodes a polymorphic ribonuclease (S-RNase), which is essential for identifying self-pollen. However, the S-RNase system has not been fully characterized. In this study, the self-S-RNase inhibited the Ca2+-permeable channel activity at pollen tube apices and the selectively decreased phospholipase C (PLC) activity in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 90 publications
0
21
0
Order By: Relevance
“…Therefore, it is generally accepted that the S-RNase causes pollen tube lethality in Pyrus solely by degrading pollen tube RNA (McClure et al., 1990; Huang et al., 1994; DeFranceschi et al., 2012). However, increasing evidence indicates that the S-RNase may act as a trigger for biochemical processes that eventually lead up to pollen tube rejection instead of directly causing it via RNA degradation (Wang et al., 2010; Wang and Zhang, 2011; Qu et al., 2017). Several studies in Pyrus and related species showed that the S-RNase interacts with (1) F-actin (Liu et al., 2007), (2) phospholipase C (PLC) (Qu et al., 2017), and (3) pyrophosphatase (PPa) (Li et al., 2018).…”
Section: The Molecular Mechanisms Of Self-recognition and Rejection Imentioning
confidence: 99%
“…Therefore, it is generally accepted that the S-RNase causes pollen tube lethality in Pyrus solely by degrading pollen tube RNA (McClure et al., 1990; Huang et al., 1994; DeFranceschi et al., 2012). However, increasing evidence indicates that the S-RNase may act as a trigger for biochemical processes that eventually lead up to pollen tube rejection instead of directly causing it via RNA degradation (Wang et al., 2010; Wang and Zhang, 2011; Qu et al., 2017). Several studies in Pyrus and related species showed that the S-RNase interacts with (1) F-actin (Liu et al., 2007), (2) phospholipase C (PLC) (Qu et al., 2017), and (3) pyrophosphatase (PPa) (Li et al., 2018).…”
Section: The Molecular Mechanisms Of Self-recognition and Rejection Imentioning
confidence: 99%
“…According to the results of the RNA-Seq and quantitative PCR, once the compatible pollen and incompatible pollen had come into contact with the stigma, genes related to pollen tube growth regulation were significantly upregulated. We previously reported on calcium- and phospholipase C-related genes in the pollen tube that were also significantly differentially expressed in the early stage following pollination (Qu et al , 2017; Qu et al , 2016). All these factors indicate that the gametophytic self-incompatibility response of Pyrus has already been initiated after pollination, rather than when the pollen tube enters the style.…”
Section: Discussionmentioning
confidence: 99%
“…In the pear system, intake of S-RNase may cause a decrease in intracellular Ca 2+ levels probably by acting on the permeability of the plasma membrane or calcium channels [55]. It is believed that intake of self S-RNase may inhibit the activity of phospholipase C associated with the plasma membrane, which in turn converts phosphatidylinositol 4,5-bisphosphate (PIP 2 ) into inositol 1,4,5-trisphosphate (IP 3 ), an effector capable of opening calcium channels [4]. However, intake of S-RNase may also decrease the apical concentration of ROS [32].…”
Section: The Tgase-cytoskeleton Interplay As a Crucial Player Of Tmentioning
confidence: 99%
“…SI involves a pollen–pistil interaction and a cell–cell recognition system, which regulates the acceptance or rejection of pollen landing on the stigma of the same species, so that SI pollen arrests its tube elongation at a specific stage during pollination, preventing self-fertilization. A single locus controls most of SI systems, the so-called “ S locus” which presents multiple S -alleles, i.e., the pistil- S and pollen- S genes; however, the process of pollen acceptance/rejection involves various other genes, many of which still need to be identified, and many other external factors [4,5]. Up to date two major classes of SI are known at the genetic level: the gametophytic SI (GSI) and the sporophytic SI (SSI).…”
Section: Introduction: the Molecular Basis Of S-rnase-based Gametomentioning
confidence: 99%